Pertunjukan Tari Tradisi Warok Reog Ponorogo di Sanggar Warok Singo Lodro, Desa Bukit Lipai, Provinsi Riau - Iis Mutmaynah; Yahyar Erawati (Advances In Education Journal, 2025)
This study explores the traditional Warok Reog Ponorogo dance performance at Sanggar Warok Singo Lodro, Bukit Lipai Village, Batang Cenaku District, Indragiri Hulu Regency, Riau Province. The research aims to describe the structure and presentation of the dance, including its elements: movement, music, makeup, costume, floor patterns, dynamics, properties, and lighting. A qualitative descriptive method was employed using structured interviews, non-participant observation, and documentation. Data were collected from six dancers, five musicians, and audience members, with Mbah Bejo as the key informant. The findings reveal twelve distinct Warok movements accompanied by traditional Javanese instruments such as kendang, gong, bonang, saron, and trumpet. The "kolor usus" belt is a prominent property symbolizing spiritual power. The dance reflects a blend of ritual, aesthetics, and cultural identity, preserving Javanese heritage in a Riau transmigrant setting.